Azadirachta indica A. Juss. (Neem) : Protein Profiles during Reproductive Phase - Sabherwal, Suhani; Dhir, K. K. (Indian Forester, 2012)
The protein profiles in neem (A. indica) were studied during the annual reproductive flush from bud formation to seed set. Four different zones of activity observed were designated as PRO-I, PRO-II, PRO-III and PRO-IV in the zymogram. It was proposed that decreased protein expression during early pre-anthesis as well as post-pollination fruit-set was due to general inhibition of quantified protein. Besides, specific banding patterns for the various growth stages also point to a definite affect in modulating active metabolism. Hence, decreased protein activity also delayed morphological expression with faint low intensity bands. High frequency bands following flowering and ovary development were point indicators for active protein metabolism and morphogenesis. This resulted in rapid growth as well as healthy fruit-set. The zymogram pattern during such periods traced high mobility, intense zones of activity. The short regeneration phase in neem leads to pharmaceutically significant product of floral inflorescence to fruit set, therefore, it is suggested that protein profiles may be the key in regulating the reproductive phase resulting in improved morpho-physiological characteristics.